Literasi dan Sikap terkait Covid-19 dan Vaksinasinya pada Siswa Kelas 8 di Kecamatan pada Kabupaten Gunungkidul dengan Waktu Terjadinya Kasus Pertama yang Berbeda - Sinta Wahyu Susanti; Purwanti Pratiwi Purbosari (Postgraduate, University of Mataram, 2022)
Literacy and attitudes in dealing with the Covid-19 pandemic are urgently needed and must be improved to reduce Covid-19 cases. However, exploration of literacy and student attitudes related to Covid-19 and its vaccination is still rare. This study aimed to obtain an overview of literacy and attitudes related to Covid-19 and its vaccination among 8th-grade students in Ponjong Sub-District where the first case of Covid-19 occurred first among other sub-districts in Gunungkidul, and Girisubo Sub-District where the first case of Covid-19 occurred last. This type of research was descriptive research with a quantitative approach using the survey method. The data analysis technique used was inferential statistic. The results showed that in Ponjong Sub-District, 61.00% of students had a high literacy level related to Covid-19, 37.00% moderate, and 2.00% low. Meanwhile, 61.00% of students in Girisubo Sub-District had a high literacy level, 30.00% moderate, and 9.00% low. On the aspect of attitude, 87.00% of the students in Ponjong Sub-District were at a good level, 7.00% were moderate, and 6.00% were poor. Meanwhile, 89.00% of students in Girisubo Sub-District were at a good level, 6.00% were moderate, and 5.00% were poor. Based on Mann-Whitney U-test (p= 0.314), there was no significant difference in student literacy and attitudes related to Covid-19 and its vaccination between 8th-grade students in Ponjong and Girisubo Sub-Districts with different time of occurrence of the first case.